Mycoplasma hominis as a cause of septic hip arthritis in a neonate. Issue 4 (12th August 2015) - Suzuki, Ryo; Takeuchi, Kazuo; Gunji, Tetsuki; Murayama, Yumiko; Ando, Akiko; Hasegawa, Junichi; Saitoh, Akihiko
Abstract : Introduction: Mycoplasma hominis frequently colonizes the adult genitourinary tract and causes significant diseases such as chorioamnionitis in adults. It also causes systemic infections such as pneumonitis and meningoencephalitis in neonates via vertical transmission. Here, we present a case of septic hip arthritis in a full-term neonate born to a woman who had intrapartum fever with premature rupture of the membranes. Case presentation: A 0-day-old newborn female, whose mother had a significant history of intrapartum fever and 52 h of premature rupture of the membranes, developed a fever after birth. Empiric antimicrobial therapy was initiated for sepsis; however, the fever did not subside. Subsequently, she developed a subcutaneous scalp abscess and right hip joint arthritis despite continued cell-wall-active antimicrobial therapy. Blood and scalp lesion samples were found to be positive by bacterial culture, and pinpoint non-haemolytic colonies were observed on blood agar plates; however, no organisms were observed by Gram staining. Microbiological analyses using Mycoplasma -specific growth plates demonstrated that the samples were positive for Mycoplasma hominis, and PCR analysis was positive for 16S rRNA in blood, abscess and joint fluid samples. The patient was treated with surgical debridement and a 3-week course of clindamycin and was discharged from hospital without sequelae. Conclusion: To the best of our knowledge, this is the first report of M. hominis causing septic hip arthritis in a neonate. Therefore, M. hominis should be included as a causative organism when treatment with empiric antimicrobial therapy is not effective in septic neonates.